Isolation, characterization, and pathogenicity of a Vibrio parahaemolyticus strain causing translucent post-larvae disease in Penaeus vannamei outside China - Nguyen Dinh-Hung; Hung N. Mai; Maiya Matthews; Harris Wright; Arun K. Dhar (PLoS ONE, 2025)
Translucent post-larvae disease (TPD) has emerged as a severe threat to shrimp aquaculture, causing substantial economic losses. The causative agent, Vibrio parahaemolyticus, has been primarily identified in China, but this study provides the first confirmed report of its presence in shrimp populations outside China. This research characterizes V. parahaemolyticus strain AG1 (VpTPD AG1), isolated from diseased Penaeus vannamei, through biochemical, molecular, and pathogenic analyses. PCR screening of VpTPD AG1 detected vhvp-1 and vhvp-2, genes previously linked to TPD virulence, while pirA/pirB genes associated with acute hepatopancreatic necrosis disease (AHPND) were absent. Experimental immersion challenges demonstrated high virulence and dose-dependent pathogenicity, with an LC50 of 8.51 × 102 CFU/mL at 96 hours in 15-day-old post-larvae (PL15) of Penaeus vannamei shrimp. Larger post-larvae (PL30) exhibited reduced susceptibility, suggesting a size-dependent resistance mechanism. Histopathological analysis confirmed the degeneration of the hepatopancreas, including tubular necrosis, epithelial cell sloughing, and bacterial invasion, consistent with previously reported TPD pathology. Additionally, hemocytic enteritis, a characteristic histopathological feature associated with infection with VpTPD AG1 strain, was marked by mucosal epithelium loss, intense inflammation, and a thick hemocyte layer in the intestine. Antibiotic susceptibility testing of VpTPD AG1 strain revealed resistance to β-lactams but sensitivity to multiple other antimicrobial classes. These findings highlight the expanding geographical distribution of VpTPD, its distinct pathological features compared to AHPND, and further highlight the urgent need to enhance surveillance and implement effective biosecurity measures to prevent its global dissemination.